Answer: x = -2 and y = -6
Step-by-step explanation:
x - 2y = 10 ................... I
3x + y = - 12 ................. II
Since we are to use elimination method , you have to decide whether you want to eliminate x first or y first. Let us eliminate x first, then we have to look for a way to make sure that the x in the two equations have the same coefficient . To do that, multiply equation I by 3 and equation II by 1 i.e
3 ( x - 2y = 10 ) ........... III
1 ( 3x + y = - 12) .......... IV
expanding the bracket
3x - 6y = 30 ................ III
3x + y = - 12................. IV
Since the x are having the same coefficient , we can then eliminate by subtracting equation IV from equation III
i.e
3x - 3x - 6y - y = 30 - ( -12)
-6y - y = 30 + 12
- 7y = 42
y = 42/ -7
y = -6
You will then substitute y = -6 into either equation I or II , so, substituting into equation I , we have
x - 2 ( -6) = 10
x + 12 = 10
x = -2